TRAINING EXPERIENCE: DEVELOPMENT OF RESEARCH ON EMERGENCY REMOTE EDUCATION - Monge, Karla Vanessa Contreras (2024)
In the context of the Mathematics Education career at the Universidad de Costa Rica (UCR), the importance of incorporating research tasks is highlighted. This is exemplified by the experience gained in the Methods and Research Designs course (PS-1080). Such tasks are crucial for developing the knowledge and skills necessary for the research assistance field. This paper details the experience of conducting a quantitative research study on the resources, strategies, and difficulties faced by Precalculus students during emergency remote education in 2021. The research not only contributed theoretical knowledge but also provided significant practical lessons that positively impact professional development.